Exploring masculinities in Barbie (2023) directed by Greta Gerwig - Pramaisela Lubis, Adilla (Lililacs Journal, 2024)
"Barbie" (2023), directed by Greta Gerwig and co-written with Noah Baumbach, offers a satirical exploration of masculinity in the Barbie universe. This research paper employs Raewyn Connell's "Types of Masculinity" framework to analyze the male characters, particularly Ken, and their representation of different forms of masculinity within the fantastical world of Barbieland. Critical Discourse Analysis (CDA) is used to uncover hidden beliefs and social commentary about masculinity expressed through language. The film presents a multifaceted exploration of masculinity, including hegemonic, complicit, subordinate, and marginalized types, challenging and reinforcing conventional gender expectations and contributing to a broader discourse on gender representation in contemporary cinema.